Prognostic Significance of β-Catenin, E-Cadherin, and SOX9 in Colorectal Cancer: Results from a Large Population-Representative Series - Bruun, Jarle; Kolberg, Matthias; Nesland, Jahn M.; Svindland, Aud; Nesbakken, Arild; Lothe, Ragnhild A. (Frontiers in Oncology, 2014)
Robust biomarkers that can precisely stratify patients according to treatment needs are in great demand. The literature is inconclusive for most reported prognostic markers for colorectal cancer (CRC). Hence, adequately reported studies in large representative series are necessary to determine their clinical potential. We investigated the prognostic value of three Wnt signaling-associated proteins, β-catenin, E-cadherin and SOX9, in a population-representative single-hospital series of 1290 Norwegian CRC patients by performing in situ protein expression analyses of each marker using the tissue microarray technology. Loss of membranous or cytosolic β-catenin and loss of cytosolic E-cadherin protein expression were significantly associated with reduced five-year survival in 903 patients who underwent major resection (722 evaluable tissue cores) independently of standard clinicopathological high-risk parameters. Pre-specified subgroup analyses demonstrated particular effect for stage IV patients for β-catenin membrane staining (P = 0.018; formal interaction test P = 0.025). Among those who underwent complete resection (714 patients, 568 evaluable), five-year time-to-recurrence analyses were performed, and stage II patients with loss of cytosolic E-cadherin were identified as an independent high-risk subgroup (P = 0.020, formal interaction test was not significant). Nuclear β-catenin and SOX9 protein, regardless of intracellular location, were not associated with prognosis. In conclusion, the protein expression level of membranous or cytosolic β-catenin and E-cadherin predicts CRC patient subgroups with inferior prognosis.